2010
DOI: 10.1111/j.1440-1630.1976.tb01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics of Students in Five Health Professions

Abstract: This article is about the empirical research of the relationship between the components of communicative behaviour of young people. Article describes the basic components of communicative behaviour: communicative tolerance, social communicative competence, perceptual-interactive competence. These components make it possible to investigate holistically and comprehensively communicative behaviour of a person, as well as to build a correctional program for effective social dialogue construction. We describe the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
4
5
0
Order By: Relevance
“…For example, Adamson et al (2003) considered personal factors related to career choice, and reported no differences between the SLP and medical radiation science students with regard to personality as measured by the Keirsey Temperament Sorter II. These results were comparable with the earlier findings where student in a range of allied health programmes scored similarly on the Myers-Briggs type indicator (MBTI) (Hardigan and Cohen 1998), the Edwards Personal Preference Schedule (Westbrook et al 1976) and the Bem Inventory (Nordholm et al 1978). Similarly, Byrne (2007b) considered a sample of students in the physiotherapy (n = 40), occupational therapy (n = 91), social work (n = 41), SLP (n = 74) and education (n = 115) programmes at a regional university.…”
Section: Research In Health Professionssupporting
confidence: 89%
See 1 more Smart Citation
“…For example, Adamson et al (2003) considered personal factors related to career choice, and reported no differences between the SLP and medical radiation science students with regard to personality as measured by the Keirsey Temperament Sorter II. These results were comparable with the earlier findings where student in a range of allied health programmes scored similarly on the Myers-Briggs type indicator (MBTI) (Hardigan and Cohen 1998), the Edwards Personal Preference Schedule (Westbrook et al 1976) and the Bem Inventory (Nordholm et al 1978). Similarly, Byrne (2007b) considered a sample of students in the physiotherapy (n = 40), occupational therapy (n = 91), social work (n = 41), SLP (n = 74) and education (n = 115) programmes at a regional university.…”
Section: Research In Health Professionssupporting
confidence: 89%
“…These results were comparable with the earlier findings where student in a range of allied health programmes scored similarly on the Myers–Briggs type indicator (MBTI) (Hardigan and Cohen ), the Edwards Personal Preference Schedule (Westbrook et al . ) and the Bem Inventory (Nordholm et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in a return rate of 62% which compares favourably with the 52% return obtained by Westbrook et al (1976) and the 62% obtained by Radonsky (1980). Students were told that they were participating in a study looking at occupational therapy students during their course of study.…”
Section: Methodssupporting
confidence: 76%
“…health professionals and others, there are also major personality differences between groups working in related fields (Brollier, 1970), and between health professionals in different countries (Westbrook et al, 1976). (EPPS) (Edwards, 19591, Westbrook et al (1976) examined the personality characteristics of five groups of first-year health science students.…”
Section: Pesaensl Andmentioning
confidence: 99%
See 1 more Smart Citation